The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015 IEEE Frontiers in Education Conference (FIE) 2015
DOI: 10.1109/fie.2015.7344252
|View full text |Cite
|
Sign up to set email alerts
|

Case for reflection in engineering education- and an alternative

Abstract: This paper examines the use of reflections in engineering education. The paper provides a review of practices in engineering education, especially during the last century. It starts by reviewing the research and pedagogical approaches in utilization of reflections and various reflective activities in engineering education. Then the authors provide various perspectives regarding reflective activities. The first part of the paper establishes the case for featuring reflective activity in engineering education. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In our extensive experiences as engineering and design educators we have observed that design students are more adaptable to the reflective process, while engineering students need more time to adjust. Our experience indicates that dedicated practice and instructor encouragement can improve engagement for all students (Cowan, 2006;Mina et al, 2015;Mina, 2015;Cowan, 2004). Learning and design experiences are iterative processes and can be constructively linked to reflective activities leading to reasoned judgements.…”
Section: The Review Of the Cyclesmentioning
confidence: 98%
“…In our extensive experiences as engineering and design educators we have observed that design students are more adaptable to the reflective process, while engineering students need more time to adjust. Our experience indicates that dedicated practice and instructor encouragement can improve engagement for all students (Cowan, 2006;Mina et al, 2015;Mina, 2015;Cowan, 2004). Learning and design experiences are iterative processes and can be constructively linked to reflective activities leading to reasoned judgements.…”
Section: The Review Of the Cyclesmentioning
confidence: 98%
“…It is important to distinguish the dictionary definition of reflection, from cognitive reflection that occurs within academic settings [16]. Early origins can be traced back over a century to early writings by John Dewey who emphasized the importance of making experiences meaningful through connection and thinking backward and forward [19].…”
Section: Reflection In Engineering Educationmentioning
confidence: 99%
“…Mina, Cown, and Heywood's overview of the use of reflection in engineering education includes theoretical foundations and distinguishes between two different contexts for reflection --to explore larger questions such as "Who am I?" and to explore the method of engineering to improve design [8]. The former is most related to our work on vocation.…”
Section: Education About Vocationmentioning
confidence: 99%